Effects of winter cold stress on photosynthesis and photochemical efficiency of PSII of the Mediterranean Cistus albidus L. and Quercus ilex L. (Plant Ecology, 2005)

Linking isoprene with plant thermotolerance, antioxidants and monoterpene emissions - Penuelas, J.; Llusia, J.; ASENSIO, D.; MUNNÉ-BOSCH, S. (Plant, Cell & Environment, 2005)
The purpose of the present study was to test the possible plant thermotolerance role of isoprene and to study its relationship with non-enzymatic antioxidants and terpene emissions. The gas exchange, chlorophyll fluorescence, extent of photo- and oxidative stress, leaf damage, mechanisms of photo- and antioxidant protection, and terpene emission were measured in leaves of Quercus ilex seedlings exposed to a ramp of temperatures of 5 °C steps from 25 to 50 °C growing with and without isoprene (10 µL L−1) fumigation. The results showed that isoprene actually conferred thermotolerance (shifted the decrease of net photosynthetic rates from 35 to 45 °C, increased Fv/Fm at 50 °C from 0.38 to 0.65, and decreased the leaf area damaged from 27 to 15%), that it precluded or delayed the enhancement of the antioxidant non-enzymatic defence conferred by α-tocopherol, ascorbic acid or β-carotene consumption in response to increasing temperatures, and that it decreased by approximately 70% the emissions of monoterpenes at the highest temperatures. This suggests that there are inducible mechanisms triggered by the initial stages of thermal damage that up-regulate these antioxidant compounds at high temperatures and that these mechanisms are somehow suppressed in the presence of exogenous isoprene, which seems to already exert an antioxidant-like behaviour.
The following values have no corresponding Zotero field: publisher: Blackwell Science Ltd
Keywords: antioxidants; ascorbic acid; fumigation; Fv/Fm; high temperatures; isoprene; Monoterpenes; photosynthetic rates; thermotolerance; zeaxanthin; α-tocopherol; β-carotene